Inhaled treatment of COPD: a Delphi consensus statement - Ninane V (International Journal of COPD, 2017)
Vincent Ninane,1 Jean-Louis Corhay,2 Paul Germonpré,3 Wim Janssens,4 Guy F Joos,5 Giuseppe Liistro,6 Walter Vincken,7 Sandra Gurdain,8 Evelyne Vanvlasselaer,8 An Lehouck8 1Department of Respiratory Medicine, Saint-Pierre Hospital, Université Libre de Bruxelles, Brussels, 2Department of Respiratory Medicine, CHU, Liege, 3Department of Respiratory Medicine, AZ Maria Middelares, Ghent, 4Department of Respiratory Medicine, Katholieke Universiteit, Leuven, 5Department of Respiratory Medicine, Ghent University Hospital, Ghent, 6Department of Respiratory Medicine, University Hospitals Saint-Luc, Brussels, 7Department of Respiratory Medicine, University Hospital Brussels, Brussels, 8Medical Department, Novartis Pharma, Vilvoorde, Belgium Background: Global Initiative for Chronic Obstructive Lung Disease (GOLD) global strategy (2015) provides guidance for the treatment of chronic obstructive pulmonary disease (COPD) with different first-choice options per GOLD category without specification. Objectives: To evaluate the level of medical experts’ consensus on their preferred first-choice treatment within different COPD categories. Methods: A two-round Delphi Panel consisting of 15 questions was completed by Belgian pulmonologists (n=31) and European (n=10) COPD experts. Results: Good consensus was reached by both expert groups for long-acting bronchodilators instead of short-acting bronchodilators as first-choice treatment in GOLD A. Single bronchodilation with long-acting muscarinic antagonist (LAMA) was preferred over long-acting ß2-agonist (LABA) and LABA/LAMA as first-choice treatment in GOLD B and GOLD C. For GOLD D patients based on the forced expiratory volume in 1 second (FEV1)<50%, a very good consensus was reached for LAMA/LABA as first-choice treatment. For GOLD D patients based on frequent or severe exacerbations, there was a good consensus for LABA/LAMA/inhaled corticosteroids (ICS) as first choice in the Belgian group. According to the European experts, both LABA/LAMA and LABA/LAMA/ICS could be the first choice for these patients. Conclusion: Belgian and European experts recommend long-acting bronchodilators as first-choice treatment. Treatment containing ICS was found only appropriate in patients with FEV1<50% and ≥2 moderate exacerbations or 1 severe exacerbation/year. Keywords: chronic obstructive pulmonary disease, therapy, long acting muscarinic antagonist, long acting beta agonist, inhaled corticosteroids, guidelines